Coronary atheroma [14 cm] extracted from the right coronary artery during off-pump coronary artery bypass grafting (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Coronary endarterectomy is a good option for surgical revascularization in diffusely coronary artery disease. In coronary artery bypass surgery, a diffusely diseased right coronary artery is an obstruction to accomplishing complete myocardial revascularization, subsequently increasing the likelihood of a poor postoperative prognosis. Here, we report a case of extraction of a long segment coronary atheroma (14 cm) from right coronary artery during off-pump coronary artery bypass grafting using closed endarterectomy technique followed by reconstruction with saphenous venous graft.